The Role of Terms in the Use of The Uzbek Language in the Field - Mamasolieva Nilufar Suyundikovna (Genius Publishing Group, 2023)
In order to determine the influence of the expansion of the social functions of language on the stylistic use of words, this article analyzes the fact that the use of new words with stylistic coloring is limited in one or another field, they serve to express the concepts of new subjects, events, events and processes in these fields.
Keywords: language; social function; extension